KUALITAS PAPAN PARTIKEL DARI LIMBAH SERABUT KELAPA SAWIT DENGAN PEREKAT DAMAR - Riza Fahlevi; Farida Hanum Hamzah; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Palm fiber is a waste of crude palm oil processing that has not been used optimally. This study aims to obtain the best resin adhesive concentration in the manufacture of particleboard from palm oil fibers. The research was conducted experimentally using a completely randomized design (CRD) with 5 treatments and 3 replications. The treatment in this study was the ratio of oil palm fiber and resin adhesive as follows: P1 (90: 10), P2 (88: 12), P3 (86: 14), P4 (84: 16), P5 (82: 18). The data obtained were analyzed statistically using Analysis of Variance (ANOVA) and Duncan New Multiple Range Test (DNMRT) at the 5% level. The results showed that the composition of oil palm fiber and resin adhesive had a significant effect on density, water content, water absorption, thickness expansion, modulus of elasticity, and modulus of rupture. The best treatment chosen was treatment P5 with a density value of 0.93 g/cm3, water content of 4.49%, water absorption 54%, thickness development 37%, modulus of elasticity of 1283.47 kgf/cm2, modulus of lift 13.03 kgf/cm2. Keywords: Particle board, oil palm fiber, resin adhesive